2020
DOI: 10.31234/osf.io/f3jyx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stationary distribution of moral strategies in a population

Abstract: ORCIDs 0000-0001-8567-7931 (J.v.B.) 0000-0002-6621-8120 (L.C.) AbstractEvolutionary models show that human cooperation can arise through direct reciprocity relationships.However, it remains largely unclear which psychological mechanisms may proximally motivate an individual to reciprocate. Recent evidence demonstrates that psychological motives for reciprocal choices (i.e., moral strategies) differ between individuals, which raises the question whether these differences have a stationary distribution in a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Our modified version of the MSM is the first to additionally include generosity as a possible moral strategy. The distribution of the other moral strategies in the current sample is comparable with previous findings from a study that used the MSM in healthy adults (van Baar et al, 2019, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our modified version of the MSM is the first to additionally include generosity as a possible moral strategy. The distribution of the other moral strategies in the current sample is comparable with previous findings from a study that used the MSM in healthy adults (van Baar et al, 2019, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Our computational model yields motive-specific parameters that allows us to index the strength of a participant's inclination toward using a particular moral strategy such as guilt aversion (GA) and inequity aversion (IA). Prior studies that implemented this model identified four moral strategies: Inequity aversion, guilt aversion, moral opportunism, and greed (van Baar et al, 2019(van Baar et al, , 2020. To examine the construct validity of these strategies, van Baar et al (2020) asked participants to indicate their decision strategy through self-report.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This intimates that many strategic socio-economic behaviors that rely on predictions about others' future choices in novel contexts, such as competitive bargaining 45 , market entry 46,47 , and collective action 2,33,48,49 , are scaffolded by a motive-based structure learning mechanism. Given that social motives (e.g., greed) vary between individuals in the population 10,12,14,15,50 , effective inference of these motives in others is likely instrumental in achieving competitive and collaborative goals.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we examine the possibility that motives, such as greed 5 , inequity aversion 6,7 , and risk aversion 8,9 , form the building blocks of these mental models of others' behavior. Motives are plausible components of such models because they can predict behavior across contexts 10 , differ reliably between people [11][12][13][14][15] , and are inferred from an early age [16][17][18] . Studies of action understanding suggest that people can infer another's motives by observing their actions 19 .…”
Section: Introductionmentioning
confidence: 99%